An Analysis of a Cash Flow Tax for Small Business - Peter Wilson (New Zealand Government, The Treasury, 2002)
This paper analyses whether it might be possible to design a cash flow tax (CFT) for small businesses in New Zealand to replace the existing income tax. Certainly, it is feasible to design the core rules of a CFT that applies to new small businesses. As with all examples of a CFT, these rules are very simple and easy to understand and apply. Integration with existing Goods and Services Tax and Pay-As- You-Earn systems provides significant simplification potential. Designing a set of rules to define what is a "small business" is possible, although there is a risk that these rules would involve some arbitrary features. The main barrier to a CFT relates to the transition from an income tax. Research in New Zealand and overseas has been unable to develop a workable set of rules that involve acceptable fiscal, economic and compliance costs. Designing a set of transition rules from a CFT to an income tax for businesses that cease to be small also appears to be an insurmountable task. Even if the considerable difficulties with a transition could be overcome, integrating a CFT into a world where most of the economy is subject to an income tax would also pose difficulties. There is a risk that the rules needed to maintain CFT treatment on distributions to owners and financers, while at the same time protecting the income tax base, might negate significant portions of the simplification gains from a CFT. Given these difficulties, an income tax will remain necessary, if the Government wants some progressivity in the tax system and to apply "ability to pay" to determine tax liabilities.
Keywords: H25; 330; Cash flow tax; small business; tax policy